Wreading on Online Literature Platforms. (July 2022) - Kraxenberger, Maria; Lauer, Gerhard
Millions of users write and read freely accessible texts every day on online literary platforms (OLPs). Intra-platform surveys aside, only very few studies have considered the demographics of digital readers and authors. Our exploratory study of avid OLP users helps to close this research gap. We requested an international sample of OLP users (13 years and above) to complete an online questionnaire. Our survey gathered demographic data and information about participants' OLP usage, motivation, (communicative) relationship with other users, and perceptions of the positive effects of OLP usage ( Nmax = 315). Among others, our results not only reinforce the theoretical concept of wreading but also indicate that OLPs are likely to enhance the pleasure derived from writing and reading. Our data show that OLP usage is not limited to adolescent users. Reportedly, for participants from Generation Y as well as from Generation Z, the experience of creative freedom and the possibility to get direct reader feedback are major motivational factors to write on OLPs. Also, our data indicate that our surveyed writers on OLPs prefer short stories. We call for more longitudinal investigations and for a common theoretical framework, in order to strengthen future research on digital literature practices and to be able to implement the didactic potential of OLPs in the classroom.